KULLANICILARININ AKILLI TELEFONLARI DEĞERLENDİRMELERİ: KASTAMONU ŞEHİR MERKEZİNDE BİR UYGULAMA - Taner, Neslişah (Business and Management Studies: An International Journal, 2014)
In recent years, mobile phones are turned into smart phones that is known multimedia machine   from interpersonal device.These devices  known smartphones are programmable mobile phones that  offer advanced talent and features  to  consumers in their personal and business lives.In  rapidly changing mobile phone market, new generation smart phone producers  incline consumers  with also being under the sway of social influence to buy and use this new  technology .It has an important  to establish smart phones offered as multi functional devices with different features   in terms of   which criteria  of them are prefered and which features whether used or not by their consumers. The purpose of this paper is to assess smartphones in terms of their users. As a result of literature review, smartphones assesment criterias that are social needs, social influences,convenience,dependency and purchase behaviour are surveyed .200 smartphone users live in the city centre of Kastamonu are surveyed in this study.  Results via  frequency analysis,Stage Ranking Analysis and Confirmatory Factor Analysis  revealed the consumers’ smartphone preference reasons,usage  and dependendency level.Factors in the literature are confirmed by the confirmatory analysis.  Results via MANOVA analysis reveal that there are differences between smartphone users consideration in terms of their demographic features.